Family Support for Prevention of Recurrent Stroke Events for Stroke Patients - Rahmania Ambarika; Novita Ana Anggraini (Journal of Global Research in Public Health, 2022)
Someone with a history of stroke has a greater tendency to experience a repeat stroke, especially if risk factors are not addressed properly, which is one of the lack of vigilance behavior in the early detection of prevention of recurrent stroke prevention. The purpose of this study is to find out the relationship between family support and recurrence of stroke among stroke patients. This research design is correlation analytic. The population in this study were all stroke patients with accidental sampling techniques obtained 98 respondents. The independent variable is family support while the dependent variable is the incidence of recurrent stroke. The test used is rho spearment. The results showed that the majority of respondents were good family support as many as 54 respondents (55.1%). Most respondents of the first stroke were 71 respondents (72.4%). Based on the results of the analysis using the  spearment rho test. The results obtained p = 0.006 There is a relationship of family support with the recurrent of strokes. The existence of family support is a support that is able to provide emotional strength, family affection and attention to increase the spirit of making efforts to prevent recurrent strokes.